Arousal State-Dependent Alterations in Neural Activity in the Zebra Finch VTA/SNc - Yanagihara, Shin; Ikebuchi, Maki; Mori, Chihiro; Tachibana, Ryosuke O.; Okanoya, Kazuo (Frontiers in Neuroscience, 2020)
Sleep-wake behaviors are important for survival and highly conserved among animal species. A growing body of evidence indicates that the midbrain dopaminergic system is associated with sleep-wake regulation in mammals. Songbirds exhibit mammalian-like sleep structures, and neurons in the midbrain ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) possess physiological properties similar to those in mammals. However, it remains uncertain whether the neurons in the songbird VTA/SNc are associated with sleep-wake regulation. Here, we show that VTA/SNc neurons in zebra finches exhibit arousal state-dependent alterations in spontaneous neural activity. By recording extracellular single-unit activity from anesthetized or freely behaving zebra finches, we found that VTA/SNc neurons exhibited increased firing rates during wakefulness, and the same population of neurons displayed reduced firing rates during anesthesia and slow-wave sleep. These results suggest that the songbird VTA/SNc is associated with the regulation of sleep and wakefulness along with other arousal regulatory systems. These findings raise the possibility that fundamental neural mechanisms of sleep-wake behaviors are evolutionarily conserved between birds and mammals.